Pengaruh Kesadaran, Pengetahuan, dan Sanksi terhadap Kepatuhan Wajib Pajak Badan dalam Membayar Pajak Penghasilan UMKM - Hanifan, Nandrian; Ritonga, Ferdiansyah (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This study aims to examine the influence of tax awareness, tax knowledge, and tax sanctions on corporate taxpayer compliance in fulfilling income tax obligations among MSMEs in Bandung, Indonesia. Low tax compliance among businesses remains a critical issue, particularly in the MSME sector, which significantly contributes to national revenue. Employing a quantitative approach, this study distributed structured questionnaires to 100 MSME taxpayers and analyzed the data using multiple linear regression. The findings reveal that all three independent variables awareness, knowledge, and sanctions have a positive and significant effect on tax compliance. Among these, tax awareness emerges as the most influential factor. The study underscores the importance of strengthening taxpayer education and consistently enforcing sanctions to improve voluntary tax compliance. These results provide practical implications for tax authorities in designing targeted policies and educational programs to enhance taxpayer engagement, especially within the MSME sector. Additionally, the study enriches academic literature on tax behavior by validating the combined effects of psychological and regulatory factors on taxpayer compliance.